METODE ISTINBATH HUKUM ABDUL QADIR HASSAN DALAM PERKARA SHALAT - Adnin Zahir; Tutik Hamidah; Aunur Rofiq (Asy-Syari'ah, 2022)
The Legal Istinbath Methodology has a very strong influence on the legal products issued. Not everyone is able to practice an Islamic law because that person is required to master various branches of science, all of which lead to a process of establishing a law. Abdul Qadir Hassan is one of the scholars of Persatuan Islam’s organization (PERSIS) who consistently refers to the Qur'an and as-Sunnah. This study aims to determine the flow of his legal Istinbath methodology in answering various problems especially in salat problem’s in the period 1958-1984. With this research, we can also understand the flow of fatwa determination from the PERSIS Hisbah Council. This study uses a library research method using library materials in the form of articles and books. The analysis technique used is content analysis, which is a research methodology that utilizes a set of procedures to draw appropriate conclusions from a document. The results of the study reveal that the position of the Qur'an and as-Sunnah is the main foundation in determining his law. In understanding a text, it is basically textual as long as there is no other information that turns it away. In addition, the existence of Ijma' Companions and Qiyas are also used in establishing a law, although qiyas in this case is not used in matters of worship. As for the opinion of the imam of the madzhab, he does not use it if he does not find its basis in the Qur'an or as-Sunnah, but is used in its function as a reinforcement of the opinion that he issues. Abdul Qadir Hassan's method indirectly leads us to be critical and distance ourselves from taqlid and also being able to revise legal decisions that have been set by previous scholars.